Surface properties and flexural strength of a monolithic zirconia submitted to grinding and regenerative heat treatment - Fratucelli, Érick Dante de Oliveira [UNESP] (2021)
The present study evaluated the average (Ra) and total (Rz) roughness, crystallography (XRD), flexural strength (FS), and Weibull modulus (m) of a monolithic zirconia subjected to grinding (G) and heat treatments (HT). Specimens were submitted or not to grinding with a diamond stone in low rotation. HT was conduced in two protocols, one at 900°C for 60 minutes and the other at 1000°C for 30 minutes. Roughness was evaluated in a profilometer, crystallography in X-ray diffractometer, and FS by four-point flexural strength in a mechanical testing machine. Grinding increased Ra, Rz, and FS. HT had no influence on roughness and for the FS, just decreased in the group that was ground and heat treated with 1000°C for 30 minutes. Neither G nor HT changed the m of the groups. In addition, the HT was able to reverse all monoclinic phases. By the properties evaluated, both HTs could be done without damaging the material.